2010
DOI: 10.1097/fbp.0b013e32833e7e80
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral and neurochemical effects of chronic L-DOPA treatment on nonmotor sequelae in the hemiparkinsonian rat

Abstract: Depression and anxiety are prevalent non-motor symptoms that worsen quality of life for Parkinson's disease (PD) patients. While dopamine (DA) cell loss is a commonly proposed mechanism, the reported efficacy of DA replacement therapy with L-DOPA on affective symptoms is inconsistent. In order to delineate the effects of DA denervation and chronic L-DOPA treatment on affective behaviors, male Sprague-Dawley rats received unilateral 6-OHDA or sham lesions and were treated daily with L-DOPA (12 mg/kg + benserazi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
48
2
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 63 publications
12
48
2
2
Order By: Relevance
“…Although depression is a common non-motor symptom in PD, previous studies into depressive-like behaviors in different rat models of PD were less consistent (Winter et al, 2007;Branchi et al, 2008;Tadaiesky et al, 2008;Eskow Jaunarajs et al, 2010Santiago et al, 2010Santiago et al, , 2014Zhang et al, 2011;Delaville et al, 2012;Sourani et al, 2012;Carvalho et al, 2013;Hui et al, 2014). The discrepancy could be related to the site of 6-OHDA injection, the extent of DA depletion, unilateral or bilateral lesions, used depression paradigms and time frame for the behavior tests.…”
Section: Depressive-like Behaviors Involve Increased Burst-firing Actmentioning
confidence: 85%
See 1 more Smart Citation
“…Although depression is a common non-motor symptom in PD, previous studies into depressive-like behaviors in different rat models of PD were less consistent (Winter et al, 2007;Branchi et al, 2008;Tadaiesky et al, 2008;Eskow Jaunarajs et al, 2010Santiago et al, 2010Santiago et al, , 2014Zhang et al, 2011;Delaville et al, 2012;Sourani et al, 2012;Carvalho et al, 2013;Hui et al, 2014). The discrepancy could be related to the site of 6-OHDA injection, the extent of DA depletion, unilateral or bilateral lesions, used depression paradigms and time frame for the behavior tests.…”
Section: Depressive-like Behaviors Involve Increased Burst-firing Actmentioning
confidence: 85%
“…Previous studies into depressive-like behaviors in 6-hydroxydopamine (6-OHDA)-lesioned rats have been limited and divergent. These studies reported increased or unchanged depressive-like behaviors in different 6-OHDA rat models of PD (Winter et al, 2007;Branchi et al, 2008;Tadaiesky et al, 2008;Eskow Jaunarajs et al, 2010Santiago et al, 2010Santiago et al, , 2014Zhang et al, 2011;Delaville et al, 2012;Sourani et al, 2012;Carvalho et al, 2013;Hui et al, 2014). Further, a dysfunctional 5-HT system is generally regarded as a risk factor for depression, and accumulating lines of evidences also suggest that degeneration of the nigrostriatal pathway leads to an impairment of 5-HT system, with evidence including the loss of 5-HT neurons, reduction of brain 5-HT content, hyperactivity of 5-HT neurons and alterations in various types of 5-HT receptors (Scholtissen et al, 2006;Wang et al, 2009;Huot et al, 2011).…”
Section: Introductionmentioning
confidence: 94%
“…Chronic L-dopa specifically affected the caudal extent of the dorsal DRN and the PFC, two brain regions involved in affective behaviors (Lowry et al, 2005(Lowry et al, , 2008Warden et al, 2012;Albert et al, 2014). The crosstalk between these two regions is involved in fear and anxiety responses in rats (Hashimoto et al, 1999;Bishop et al, 2004;Amat et al, 2005;Forster et al, 2006) and several preclinical and clinical studies propose that chronic L-dopa therapy for Parkinson's disease could result in mood disturbances, such as anxiety and depression (Damasio et al, 1971;Choi et al, 2000;Borah and Mohanakumar, 2007;Eskow Jaunarajs et al, 2010. These mood disturbances may be attributable to an underlying dysregulation of the monoaminergic systems within limbic regions as demonstrated in rats (Eskow Jaunarajs et al, 2012) and more recently in monkeys (Engeln et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As discussed earlier, neurodegeneration of LC neurons in PD is a well established phenomenon that precedes DA neuronal loss (Braak et al, 2003). It has been postulated that a compromised LC produces significant changes in NE receptors and transporters that may lead to the development or exacerbation of depression/anxiety (Eskow Jaunarajs et al, 2010). Additionally, Remy et al (2005) have reported reduced binding for the DA/NE transporter, suggesting a loss of terminals, in the LC of PD patients suffering from anxiety and depression (Remy et al, 2005).…”
Section: Non-motor Symptoms 221 Ne Loss and Non-motor Symptomsmentioning
confidence: 99%
“…In a rodent model of PD, alterations in DA and NE systems in the striatum have been reported to produce anxiety (Tadaiesky et al, 2008), consistent with findings in naĂŻve rats that NE regulates anxiety behavior. Experimental studies have reported depression and anxiety-like behaviors in a 6-OHDA lesion model of PD (Branchi et al, 2010;Eskow Jaunarajs et al, 2010;Tadaiesky et al, 2008). Additionally, concomitant depletion of NE, 5-HT and DA in a unilateral rodent model of PD produced symptoms of depression, suggesting that loss of all three systems contribute to PD-like depression (Delaville et al, 2010).…”
Section: Non-motor Symptoms 221 Ne Loss and Non-motor Symptomsmentioning
confidence: 99%